Development of a Scrabble Board Game Based on Experiential Learning for Enhancing Arabic Vocabulary Acquisition - Khansa Nabila; Agus Yasin; Alif Cahya Setiyadi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
This research seeks to create a Scrabble Board Game grounded in Experiential Learning principles to improve Arabic vocabulary acquisition for novice students. The study utilized a Research and Development (R&D) methodology based on the ADDIE model, which encompasses the stages of Analysis, Design, Development, Implementation, and Evaluation. In the development phase, a prototype was produced and evaluated by three specialists in Arabic language, educational media, and pedagogical practice, attaining an average score of 4.6 (very valid). The study encompassed 20 second-grade children at Madrasah Ibtidaiyyah across three sessions, utilizing pre-test and post-test evaluations to determine learning results. The findings indicated a notable enhancement in vocabulary proficiency, with the mean score rising from 54.3 to 82.1 and an N-Gain score of 0.61, categorizing it as moderate to high. Observations and interviews validated heightened student engagement, motivation, and teamwork. Kolb’s Experiential Learning Model enabled significant learning through practical activities, reflection, and application. This study concludes that the integration of educational games with experiential learning methodologies can significantly enhance Arabic vocabulary acquisition and foster a more dynamic classroom atmosphere. Future research is advised to investigate digital adaptations and broader deployment in diverse educational settings.